2013
DOI: 10.4012/dmj.2013-053
|View full text |Cite
|
Sign up to set email alerts
|

The effects of glass ionomer and flowable composite liners on the fracture resistance of open-sandwich class II restorations

Abstract: This in vitro study aimed to investigate the effects of glass-ionomer and flowable composite liners on the fracture resistance of Class II amalgam and composite restorations. Group 1 cavities were restored with amalgam and Group 4 cavities with nanofill composite after the application of a dentin-bonding agent. For the remaining groups, light-cured-glass-ionomer liner was used in a gingival floor proximal box (Groups 2, 5) or flowable composite was used as a liner (Groups 3, 6), the remainder of the cavity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…With the development of new adhesives, resin composites are rapidly becoming the primary restorative material for direct restoration of posterior or anterior teeth due to their ability to bond to the dental structure. [ 1 2 ] Especially for Class II restorations, resin composites are the first choice in clinics.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of new adhesives, resin composites are rapidly becoming the primary restorative material for direct restoration of posterior or anterior teeth due to their ability to bond to the dental structure. [ 1 2 ] Especially for Class II restorations, resin composites are the first choice in clinics.…”
Section: Introductionmentioning
confidence: 99%
“…In a study with experimental design similar to our study, 0.5 mm RMGI and conventional flowable composite liner could increase fracture resistance of premolars with P60 composite resin restoration . However, no increase was observed in a study by Guray Efes et al, in which 1 mm of liner was placed on the gingival floor . The volumetric polymerization shrinkage with the elastic modulus affected the total stress on the restored teeth in opposite ways .…”
Section: Discussionmentioning
confidence: 97%
“…The latter has additional benefits such as fluoride release, self‐adhesiveness, and less technique sensitivity . However, capability of absorbing the polymerization shrinkage stress by these liners and their subsequent effects on cuspal deflection and fracture resistance have been reported with conflicting results. The weakening effect of RMGI base or liner on the strength of the restoration and its resultant higher fracture rate was demonstrated by clinical studies on the longevity of composite restorations …”
mentioning
confidence: 99%
“…Previous studies have reported that placement of a flowable liner reduces the microleakage and increases the bond strength and fracture resistance values [ 15 , 16 ]. Koliniotou-Koumpia et al [ 17 ] reported that the use of a flowable composite as a liner 0.5 mm in thickness reduced microleakage and internal void formations and enhanced the internal adaptation as shown in the SEM in class V composite restorations.…”
Section: Discussionmentioning
confidence: 99%